A content analysis on family firms' association annual questionnaire - Kokko, Tanja (2010)
The aim of this paper is to analyze the content of a questionnaire that is used in order to conduct a Finnish Family Firms’ Association’s annual barometer for its members. The content of the questionnaire is reflected to a relevant theory and compared with two other fairly similar questionnaires. Based on the analysis, reflections, and comparisons some suggestions for questionnaire modification are presented. The research question concerns what kind of data may be essential to measure among Finnish family firms. This paper aims at enhancing the Finnish Family Firms’ Association to conduct a questionnaire that may allow even deeper understanding on the situation and position of family businesses in Finland. The research concludes that the present questionnaire is very adequate and the topics handled very appropriate. Nevertheless, it is possible to develop the questionnaire even further. The main argument behind the need for development is the fact that the Family Firms’ Association has been using somewhat unchanged questionnaires for the past ten years. The world has changed and the family firms may have to adjust according. It is reasonable for the questionnaire to keep up with the phase as well.